Constant rate infusion of diazepam or propofol for the management of canine cluster seizures or status epilepticus - Cagnotti, Giulia; Ferrini, Sara; Muro, Giorgia Di; Borriello, Giuliano; Corona, Cristiano; Manassero, Luca; Avilii, Eleonora; Bellino, Claudio; D'Angelo, Antonio (Frontiers in Veterinary Science, 2022)
Cluster seizures (CS) and status epilepticus (SE) in dogs are severe neurological emergencies that require immediate treatment. Practical guidelines call for constant rate infusion (CRI) of benzodiazepines or propofol (PPF) in patients with seizures not responding to first-line treatment, but to date only few studies have investigated the use of CRI in dogs with epilepsy. The present retrospective study aimed to describe the use of two types of CRI in dogs with refractory seizure activity. A total of 37 dogs, with 50 instances of hospitalization and CRI administered for CS or SE were included in the study. CRI of diazepam (DZP) or PPF was administered in 29/50 (58%) and in 21/50 (42%) instances of hospitalization, respectively. Idiopathic epilepsy was diagnosed in 21/37 (57%), (13/21 tier I and 8/21 tier II); structural epilepsy was diagnosed in 6/37 (16%) of which 4/6 confirmed and 2/6 suspected. A metabolic or toxic cause of seizure activity was recorded in 7/37 (19%). A total of 38/50 (76%) hospitalizations were noted for CS and 12/50 (24%) for SE. In 30/50 (60%) instances of hospitalization, the patient responded well to CRI with cessation of seizure activity, no recurrence in the 24 h after discontinuation of CRI through to hospital discharge, whereas a poor outcome was recorded for 20/50 (40%) cases (DZP CRI in 12/50 and PPF CRI in 8/50). Comparison between the number of patients with favorable outcome and those with poor outcome in relation to type of CRI, seizure etiology, reason for presentation (CS or SE) sex and previous AED therapy was carried out but no statistically significant differences were found. The present study is the first to document administration of CRI of DZP or PPF in a large sample of dogs with epilepsy. The medications appeared to be tolerated without major side effects and helped control seizure activity in most patients regardless of seizure etiology. Further studies are needed to evaluate the effects of CRI duration on outcome and complications.